Different reactor configurations for enhancement of CO2 methanation - Harkou, Eleana; Hafeez, Sanaa; Adamou, Panayiota; Zhang, Zhien; Tsiotsias, Anastasios I.; Charisiou, Nikolaos D.; Goula, Maria A.; Al-Salem, Sultan Majed; Manos, George; Constantinou, Achilleas (My University, 2023)
Greenhouse gas emissions are a massive concern for scientists to minimize the effect of global warming in the environment. In this study, packed bed, coated wall, and membrane reactors were investigated using three novel nickel catalysts for the methanation of CO2. CFD modelling methodologies were implemented to develop 2D models. The validity of the model was investigated in a previous study where experimental and simulated results in a packed bed reactor were in a good agreement. It was observed that the coated wall reactor had poorer performance compared to the packed bed, approximately 30% difference between the results, as the residence time of the former was lower. In addition, two membrane configurations were proposed, including a membrane packed bed and membrane coated wall reactor. Additional studies were performed in the coated wall reactor revealing that lower flow rates lead to higher conversion values. As for the bed thickness the optimum layer was found to be 1 mm. In both membrane reactor configurations, the effect of the thickness of M1 membrane, which indicates the membrane for the removal of H2O, didn't show difference while the reduction of the thickness of M2 membrane, which indicates the membrane for the removal of CO2, H2 and H2O, showed better results in terms of conversion.
Keywords: CFD modelling; CO2 methanation; Coated wall reactor; Membrane reactor; Packed bed reactor